Karakteristik Pelanggan Dan Persepsi Pelanggan Terhadap Pelayanan Puskesmas (Kasus di Kota Kotamobagu dan Kabupaten Bolaang Mongondow Utara, Provinsi Sulawesi Utara) - Mutu G Mokoginta; Basita G Sugihen; Djoko Susanto; Pang S Asngari (Jurnal Penyuluhan, 2009)
Clients characteristics and clients perception to the Community health service has been considered as two important aspects. Clients characteristics measured by age, income, works, sex, education background, number of families, distances to community health service, the understanding of mean, goal, and benefit for healthy life. Clients perception to the Community health service measured by medical worker, health services and the cure that has been given has a high level category. Clients satisfaction conducted by Community Health Service tends to be high category.